Analysis of lean-agile-resilient-green (LARG) implementation in the electric car industry in Indonesia - Purba, Humiras Hardi; Jaqin, Choesnul; Aisyah, Siti; Nabilla, Mutiara (Universitas Serang Raya, 2024)
Vehicle type approval (VTA) total registration of electronic vehicles in Indonesia for the accumulation period until August 2023 is 81,525 units with a composition of 4-wheeled vehicles 18,300 units. The use of electric vehicles is still a tiny portion compared to the motorized vehicle population in Indonesia, which will reach more than 146 million units in 2022. It is different from developments in Europe, the United States, and China, where more research into the use of electric vehicles is being carried out. The readiness of the automotive industry system to produce electric vehicles is absolutely necessary to achieve superior productivity levels. National autoÂmotive companies need to anticipate that changes in production systems will also change along with changes in processes and components in electric vehicles. In the next few years, world-class manufacturing production systems will refer to LARG (lean, agile, resilient, and green) aspects. Lean, agile, resilient, and environmentally friendly manufacturing industrial operaÂtions are critical. This research aims to determine the level of appliÂcation of LARG aspects in the electric vehicle automotive industry. The method used was exploratory, and a questionnaire was filled out with industry experts and analyzed using the analytical hierarchy process (AHP) and objective matrix (OMAX). The results of this study confirm that all aspects of LARG require improvement. Resilience (R) and green (G) have performance below 10 percent, so these two aspects are priorities for improvement by the electric car industry in Indonesia.